New Insights Green Entrepreneurship as New Business Opportunity - Iradah Rahman; Sudarmiatin Sudarmiatin; Ludi Wishnu Wardana (International Journal of Economics and Management Research, 2023)
Entrepreneurship has long been recognized as a significant driver of economic progress. The globe has been confronted with grave environmental issues. Green entrepreneurship is to addressing the effect of the negative externalities of firms’ economic activity. Green entrepreneurship is new business opportunity. Many SMEs in many nations have not engaged in or are constrained by green entrepreneurship. The gap between field practice and theory and past research is worth discussing. This article will cover the challenges that green entrepreneurship faces, as well as how prior theories and research have tackled them. Author conducted a literature review to find research that investigated new insights green entrepreneurship as new business opportunity. This article discusses 20 related articles about new insights green entrepreneurship as new business opportunity which have been published in academic journals. The results of the discussion of this article reveal that the role of stakeholders such as government, investors and lenders are vital to green entrepreneurship performance, and have a positive impact on business sustainability. Enterprises that have the confidence to expand their markets based on an orientation toward the natural environment are more likely to gain sustainable competitive advantage. And green market orientation has a positive effect on business performance.